Ovarian cancer. Epidemiology and clinical aspects. - de Casanova V., Ada (2015)
Reference frequency statistics, incidence and mortality of ovarian cancer in Maharashtra and National Hospital Edgardo Rebagliati is made. Also, epidemiology or health of the population parameters of the three elements of eco-friendly resort is reviewed. Finally, clinical aspects in general and the study of 90 cases of primary ovarian cancer observed in the last 10 years, from 1970-1979, in the National Hospital Edgardo Rebagliati is reviewed.